2019
DOI: 10.3892/mmr.2019.9876
|View full text |Cite
|
Sign up to set email alerts
|

Cx32 mediates cisplatin resistance in human ovarian cancer cells by affecting drug efflux transporter expression and activating the EGFR‑Akt pathway

Abstract: Our previous study demonstrated that connexin 32 (Cx32) was upregulated and redistributed to the cytoplasm in A2780 human ovarian cancer cells with acquired resistance to cisplatin; this increased Cx32 feedback promoted cisplatin resistance. To further investigate the mechanism underlying Cx32-mediated cisplatin resistance, alterations in drug transporters, the DNA repair system and the anti-apoptotic signalling pathway were investigated by overexpressing or knocking down Cx32 in parental cells (A2780); cispla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…In combination, both influx and efflux pathways can contribute to drug resistance [63]. For example, cisplatin-resistant A2780Cis cells exhibit downregulation of a copper uptake transporter protein (CTR1) and upregulation of efflux transporters multi-drug resistance protein 2 (MRP-2), ATPase copper transporting α (ATP7A), and ATPase copper transporting β [65].…”
Section: Cellular Accumulation Of Rutheniummentioning
confidence: 99%
“…In combination, both influx and efflux pathways can contribute to drug resistance [63]. For example, cisplatin-resistant A2780Cis cells exhibit downregulation of a copper uptake transporter protein (CTR1) and upregulation of efflux transporters multi-drug resistance protein 2 (MRP-2), ATPase copper transporting α (ATP7A), and ATPase copper transporting β [65].…”
Section: Cellular Accumulation Of Rutheniummentioning
confidence: 99%
“…Kawasaki et al and Li et al reported that cytoplasmic accumulation of Cx32 expanded the cancer stem cell population and enhanced the motility and metastatic ability of human hepatoma cells (9,10). Studies performed by our team demonstrated that upregulated Cx32 in cervical ovarian and liver cancer cells was mainly localized in the cytoplasm and produced anti-apoptotic and pro-tumor effects in a GJ-independent manner (11)(12)(13)(14). Nevertheless, the mechanism of the upregulation and internalization of Cx32 remains unknown.…”
Section: Inhibition Of Ubiquitin-specific Protease 14 Promotes Connexmentioning
confidence: 80%
“…As shown in Figure 8 , the PPI network indicated that SLC7A11 directly interacted with 16 proteins, and indirectly interacted with the remaining 15 proteins. All the 16 proteins have been reported to be implicated in the modulation of drug resistance in OC, namely ABCC1 ( 48 ), ABCC2 ( 49 ), ABCB1 ( 50 ), CD44 ( 51 ), ALDH1A1 ( 52 ), ABCG2 ( 53 ), PROM1 ( 54 ), CDKN1A ( 55 ), CDH1 ( 56 ), EGFR ( 57 ), BRCA1 ( 58 ), BRCA2 ( 58 ), BCL2L1 ( 59 ), MDM4 ( 60 ), MTOR ( 61 ), and BRAF ( 62 ); and among the 15 proteins, nine of them were reported to be implicated in drug resistance, which were ERCC1 ( 63 ), MVP ( 64 ), ERBB2 ( 65 ) TP53 ( 66 ), PARP1 ( 58 ), MSH3 ( 67 ), BCL2 ( 68 ), CASP3 ( 69 ), and PTEN ( 70 ). The results above indicated that among the 31 proteins, SLC7A11 interacted with 25 OC drug resistance-related proteins, providing strong PPI network evidence to support the relationship between SLC7A11 and drug resistance in OC.…”
Section: Resultsmentioning
confidence: 99%